PENGGUNAAN APLIKASI SIPAKAR DALAM PENGENDALIAN KARHUTLA DI PROVINSI RIAU - Rendy Dila Wiguna; Dwiyola Indah Ramadhani; Fadil Dwi Herfian; M. Gading Saputro; Raddana Raddana (LPSDI Bina Patria, 2022)
Riau Province is one of the provinces where forest and land fires often occur during the dry season. The peak of the forest and land fires in Riau Province occurred in 2014 and 2015, as a result of these events, namely transportation damage, health, economic and environmental problems. The SIPAKAR application is an application created by the Regional Disaster Management Agency (BPBD) of Riau Province to find out the coordinates of forest and land fires that occurred in Riau Province. To understand in detail how the use of the SIPAKAR application in controlling forest and land fires in Riau Province is the purpose of this study. This study uses a qualitative approach that uses interview, documentation, and observation techniques to collect data together with the Regional Disaster Management Agency (BPBD) of Riau Province. BPBD Riau Province can find out the time, location, area of ​​the area indicated by the disaster through the SIPAKAR application. In addition, the Riau Province BPBD continues to develop and modify the SIPAKAR application until now the SIPAKAR application can also indicate disasters that often occur in Riau Province apart from Karhutla, such as floods and landslides.